A titanium-containing gas-phase ultrastable mesoporous Y zeolite and its preparation method and application
Through gas solid reactions and subsequent processing steps, prepare the titanium -containing gas -containing hyper -stable intermediary Y boilestone, solving the problem of high cost and complex process of existing technology intermediary hole Y -shaped boiler, and achieved efficient catalytic cracking performance and low cost Production.
Patent Information
- Application Number
- CN202110139434.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-01
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-02-01
AI Technical Summary
The existing technology has high preparation cost and complex process and takes a long time, making it difficult to meet the demand for efficient catalytic cracking in the refining industry.
By reacting the gas -solid reaction of micropore Nay and titanium titanium gas, combined with deodorizing water washing and drying steps to prepare titanium -containing gas -containing super -stable interlative holes Y boiler. This method simplifies the process and reduces energy consumption and production costs.
The introduction of metors and titanium atoms is simply introduced, which improves the catalytic performance of the Y -shaped boiler, enhances the capacity of heavy oil conversion and light oil receipts, and reduces production costs.
Smart Images

Figure CN114835135B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of zeolite catalysts, and relates to a titanium-containing gas-phase ultrastable mesoporous Y zeolite, a preparation method of the titanium-containing gas-phase ultrastable mesoporous Y zeolite, and an application of the titanium-containing gas-phase ultrastable mesoporous Y zeolite. Background Art
[0002] Catalytic cracking is an important secondary processing technology for crude oil. Therefore, the catalytic cracking process plays an important role in the processing of heavy oil and increasing the production of light oil. The importance of catalytic cracking catalyst and its main active component Y-type zeolite is self-evident. The product distribution of catalytic cracking reaction is mainly determined by the cracking activity and selectivity of Y-type zeolite. The influence of zeolite's silicon-aluminum ratio, pore structure, crystallinity and acid distribution on catalytic cracking performance has always been the focus of research and development in this field.
[0003] In recent years, the heaviness and inferiority of crude oil at home and abroad have been increasing, and the demand for light oil products in people's daily life has been rising. In order to improve the ability of catalytic cracking deep processing of heavy crude oil, the requirements of the oil refining industry for FCC catalysts are also increasing. Therefore, the Y-type zeolite as an active component needs to improve its modification method to better suit the catalytic cracking process.
[0004] Y-type zeolite is widely used in catalytic cracking reactions because of its suitable acid properties, extremely high specific surface area and excellent thermal stability. However, the microporous structure of Y-type zeolite seriously hinders the diffusion of heavy oil macromolecules in the pores, resulting in poor accessibility of its acidic active centers, which reduces the catalytic performance of Y-type zeolite as an active component of the catalyst. In order to improve the cracking ability of Y-type zeolite for heavy and inferior crude oil, it is necessary to introduce a mesoporous structure into Y-type zeolite to increase the diffusion rate of heavy oil macromolecules in the pores and improve the accessibility of its acidic active centers. It can be seen that Y-type zeolite with a mesoporous structure is very suitable for the catalytic cracking of heavy oil, which affects the product distribution and economic benefits of the catalytic cracking unit.
[0005] The existing methods for preparing mesoporous Y-type zeolite can be roughly divided into two categories, namely direct synthesis method and post-modification treatment method. There are three main post-treatment modification methods to obtain mesoporous zeolite, namely hydrothermal method, alkali treatment method and acid-base coupling treatment method.
[0006] The direct synthesis method uses an organic template to obtain a Y-type zeolite with regular and orderly mesopores, and a significant increase in the mesopore volume and external specific surface area. However, the expensive organic template greatly increases the production cost of zeolite, so there are problems of high cost and environmental pollution in large-scale industrial production.
[0007] The hydrothermal treatment method was developed in the 1960s. This method uses directly synthesized NaY zeolite as the treatment object. After ammonium exchange, it is calcined at high temperature in a water vapor atmosphere. This process is repeated twice or even multiple times, which can increase the silicon-aluminum ratio of the zeolite framework while obtaining a mesoporous structure, which can be said to kill two birds with one stone. The Y-type zeolite obtained by this method is called USY-type zeolite. However, such a method generally requires two or even multiple ammonium ion exchanges and high-temperature hydrothermal treatments, which consumes a lot of energy and requires a large amount of ammonium salt.
[0008] In 1980, Beyer first proposed the silicon tetrachloride vapor phase dealumination and siliconization method, which generally uses SiCl4 under nitrogen protection to react with dehydrated Y-type zeolite at a certain temperature. SiCl4 removes framework aluminum while inserting silicon in silicon tetrachloride to complete dealumination and siliconization. The high-silicon zeolite obtained by this method can effectively avoid the generation of hydroxyl vacancies when Y-type zeolite is subjected to dealumination and siliconization reaction under hydrothermal conditions, avoid the disadvantages of lattice collapse and structural destruction, and thus can prepare zeolite with high crystal retention and high thermal stability.
[0009] The alkali treatment method and acid-base coupling treatment method for manufacturing mesoporous structures are both based on SiCl4 to increase the silicon-aluminum ratio of the Y-type zeolite framework, and the process is relatively long.
[0010] The newly developed alkali treatment method in recent years can effectively regenerate mesopores, but this method is suitable for zeolites with high silicon-aluminum ratios (such as ZSM-5, silicon-aluminum oxide molar ratio of 25). For aluminum-rich Y-type zeolite, if you want to use this method, you must first increase the skeleton silicon-aluminum ratio of the zeolite. Patent CN104843736A uses this method to prepare Y-type zeolite containing a mesoporous structure. Patent CN104760973A uses an acid-base coupling treatment method to prepare Y-type zeolite containing ultra-high mesoporous content. This method significantly shortens the process compared to the hydrothermal method and significantly reduces energy consumption. However, three steps are still required to obtain mesoporous Y zeolite, namely, the ultra-stable silicon tetrachloride gas phase of NaY, acid treatment, and alkali treatment.
[0011] In summary, the art still lacks a technology for preparing mesoporous Y zeolite with the characteristics of low cost, low energy consumption, short process and short time. Summary of the invention
[0012] The main purpose of the present invention is to provide a titanium-containing gas-phase ultrastable mesoporous Y zeolite and a preparation method and application thereof, so as to solve the defects of the prior art such as high preparation cost, complex process and long time consumption of mesoporous Y zeolite.
[0013] In order to achieve the above object, the present invention provides a method for preparing a titanium-containing gas-phase ultrastable mesoporous Y zeolite, the preparation method comprising the following steps:
[0014] Step 1, subjecting microporous NaY zeolite to a gas-solid reaction with titanium tetrachloride gas at a reaction temperature of 350 to 550° C. and a reaction time of 10 to 240 minutes; and
[0015] Step 2: Wash the NaY zeolite after the reaction in step 1 with deionized water, filter and dry to obtain titanium-containing gas-phase ultrastable mesoporous Y zeolite.
[0016] The method for preparing the titanium-containing gas-phase ultrastable mesoporous Y zeolite of the present invention comprises the following steps: the silicon-aluminum molar ratio of the microporous NaY zeolite is 4.5 to 5.5, the dry basis Na2O content of the microporous NaY zeolite is 11 to 14 wt %; the total pore volume of the microporous NaY zeolite is not less than 0.250 cm 3 / g, BET specific surface area not less than 550m 2 / g.
[0017] The preparation method of the titanium-containing gas-phase ultrastable mesoporous Y zeolite of the present invention, wherein the microporous NaY zeolite contains rare earth elements, the rare earth elements are calculated as RE2O3, the dry basis rare earth element content of the microporous NaY zeolite is 1-10wt%, and the Na2O content is not less than 5wt%; and / or the rare earth elements are one or both of lanthanum and cerium.
[0018] The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite of the present invention further comprises a step of drying the microporous NaY zeolite before the microporous NaY zeolite and titanium tetrachloride gas undergo a gas-solid reaction.
[0019] The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite of the present invention comprises the following steps: the titanium tetrachloride gas is introduced into the microporous NaY zeolite under the influence of a dry gas to carry out a gas-solid reaction; the dry gas is one or a combination of two or more selected from the group consisting of nitrogen, air, argon and helium.
[0020] The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite of the present invention comprises the following steps: the mass ratio of the titanium tetrachloride gas to the microporous NaY zeolite dry basis is 0.1-0.8:1.
[0021] The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite of the present invention comprises the following steps: silicon tetrachloride gas is mixed with the titanium tetrachloride gas, and the mass ratio of the titanium tetrachloride gas to the silicon tetrachloride gas is not less than 4:1; and the mass ratio of the sum of the mass of the titanium tetrachloride gas and the silicon tetrachloride gas to the dry basis of the microporous NaY zeolite is 0.1 to 0.8:1.
[0022] The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite of the present invention comprises a gas-solid reaction between microporous NaY zeolite and titanium tetrachloride gas, including a stage of gas-solid reaction between microporous NaY zeolite and continuously added titanium tetrachloride gas, and a reaction stage of microporous NaY zeolite under dry gas purge after the addition of titanium tetrachloride gas is stopped.
[0023] The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite of the present invention comprises the following steps: the reacted NaY zeolite is washed with deionized water, and the mass ratio of the NaY zeolite to the deionized water is 1:5-10.
[0024] In order to achieve the above object, the present invention also provides titanium-containing gas-phase ultra-stable mesoporous Y zeolite obtained by the above-mentioned preparation method of titanium-containing gas-phase ultra-stable mesoporous Y zeolite.
[0025] The titanium-containing gas-phase ultrastable mesoporous Y zeolite of the present invention has a total pore volume of 0.324 to 0.376 cm 3 / g, and the mesopore volume is 0.079~0.197cm 3 / g, and the proportion of mesopore volume to total pore volume is 21.0-60.8%.
[0026] In order to achieve the above object, the present invention further provides the use of the above titanium-containing gas-phase ultrastable mesoporous Y zeolite as an acidic active component of a catalytic cracking catalyst.
[0027] Beneficial effects of the present invention:
[0028] The present invention introduces a considerable amount of mesoporous and heteroatom titanium into Y-type zeolite through a simple process, while retaining more acidic centers of Y-type zeolite. Compared with the existing method for preparing mesoporous Y-type zeolite, the reaction process is shortened, the reaction time is reduced, the energy consumption is reduced, and the production cost can be saved. Moreover, the heavy oil conversion capacity of the FCC catalyst prepared with such Y-type zeolite as the active component is enhanced, and the yield of light oil is improved.
[0029] Instruction Manual
[0030] Figure 1 The XRD spectra of Y zeolite obtained in Examples 1, 5 and 6 of the present invention are shown. DETAILED DESCRIPTION
[0031] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions.
[0032] The present invention provides a method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite, the preparation method comprising the following steps:
[0033] Step 1, subjecting microporous NaY zeolite to a gas-solid reaction with titanium tetrachloride gas at a reaction temperature of 350 to 550° C. and a reaction time of 10 to 240 minutes; and
[0034] Step 2: Wash the NaY zeolite after the reaction in step 1 with deionized water, filter and dry to obtain titanium-containing gas-phase ultrastable mesoporous Y zeolite.
[0035] The technical solution of the present invention is mainly to modify the microporous NaY zeolite to prepare NaY zeolite with rich mesoporous structure. The present invention does not specifically limit the preparation method of microporous NaY zeolite, and any conventional method for preparing microporous NaY zeolite in the art can be used. As a preferred technical solution, the silicon-aluminum molar ratio of the microporous NaY zeolite of the present invention is 4.5-5.5 in terms of SiO2 and Al2O3 molar ratio; preferably 4.8-5.3:1. The dry basis Na2O content of the microporous NaY zeolite of the present invention is preferably 11-14wt%; the total pore volume of the microporous NaY zeolite is preferably not less than 0.250cm 3 / g, and the BET specific surface area is preferably not less than 550m 2 / g; the total pore volume of NaY zeolite is further preferably not less than 0.300 cm 3 / g, and the BET specific surface area is further preferably not less than 650m 2 / g. The dry basis Na2O content of the microporous NaY zeolite refers to the content of Na2O based on the dry basis of the microporous NaY zeolite.
[0036] As a preferred technical solution, the microporous NaY zeolite of the present invention may also contain rare earth elements, wherein the rare earth elements are calculated as RE2O3, and the dry basis rare earth element content of the microporous NaY zeolite is 1-10wt%, and the Na2O content is not less than 5wt%. The rare earth element may be one or both of lanthanum and cerium, but the present invention is not limited thereto. The dry basis rare earth element content of the microporous NaY zeolite refers to the content of rare earth elements calculated as RE2O3 based on the dry basis of the microporous NaY zeolite.
[0037] In addition, according to the preferred technical solution of the present invention, the microporous NaY zeolite or the microporous NaY zeolite containing rare earth needs to be dried before the gas-solid reaction with titanium tetrachloride gas, and the sample is stored in a dry atmosphere environment to react with titanium tetrachloride gas. In the drying method of NaY zeolite or the NaY zeolite containing rare earth, the preferred treatment temperature is 400°C to 550°C, and the treatment time is 60 to 120 minutes.
[0038] The operation of the gas-solid reaction between the microporous NaY zeolite and the titanium tetrachloride gas of the present invention can be as follows: the titanium tetrachloride gas is introduced into the microporous NaY zeolite under the condition of being carried by a dry gas, and the gas-solid reaction is carried out in a water-free dry environment. The preferred gas-solid reaction temperature is 400-550° C., and the preferred gas-solid reaction time is 60-120 minutes. The dry gas can be one, two or more of the group consisting of nitrogen, air, argon and helium. The mass ratio of the titanium tetrachloride gas to the dry basis of the microporous NaY zeolite is 0.1-0.8:1.
[0039] In another embodiment of the present invention, the microporous NaY zeolite is subjected to a gas-solid reaction with a mixture of titanium tetrachloride and silicon tetrachloride, that is, the mixture of titanium tetrachloride and silicon tetrachloride is introduced into the microporous NaY zeolite under the influence of dry gas, and the gas-solid reaction is carried out in a water-free dry environment. The mass ratio of titanium tetrachloride gas to silicon tetrachloride gas is preferably not less than 4:1, and the mass ratio of the sum of the mass of titanium tetrachloride gas and silicon tetrachloride gas to the dry basis of the microporous NaY zeolite is 0.1 to 0.8:1.
[0040] The ratio of the titanium tetrachloride gas or the mixed gas of titanium tetrachloride and silicon tetrachloride to the dry gas in the present invention is preferably such that the titanium tetrachloride gas or the mixed gas of titanium tetrachloride and silicon tetrachloride is saturated in the dry gas.
[0041] The gas-solid reaction of the microporous NaY zeolite with titanium tetrachloride gas or titanium tetrachloride and silicon tetrachloride mixed gas of the present invention comprises: a gas-solid reaction stage of the microporous NaY zeolite and the continuously introduced titanium tetrachloride gas or titanium tetrachloride and silicon tetrachloride mixed gas, and a reaction stage of the microporous NaY zeolite under dry gas purge after the introduction of titanium tetrachloride gas or titanium tetrachloride and silicon tetrachloride mixed gas is stopped. That is, the titanium tetrachloride gas or titanium tetrachloride and silicon tetrachloride mixed gas is continuously introduced into the microporous NaY zeolite to react for a period of time, and then the introduction of titanium tetrachloride gas or titanium tetrachloride and silicon tetrachloride mixed gas is stopped, and the microporous NaY zeolite is continued to react for a period of time under the state of only continuously introducing dry gas, so that the microporous NaY zeolite can be fully reacted and the NaY zeolite can be prevented from agglomerating.
[0042] In one embodiment, the above reaction time of 10 to 240 minutes includes the time for the gas-solid reaction stage of the microporous NaY zeolite and the continuously introduced titanium tetrachloride gas, or the mixed gas of titanium tetrachloride and silicon tetrachloride, and the time for the reaction stage of the microporous NaY zeolite under dry gas purge after the introduction of titanium tetrachloride gas, or the mixed gas of titanium tetrachloride and silicon tetrachloride is stopped.
[0043] The reacted NaY zeolite is washed with deionized water, filtered and dried to obtain titanium-containing gas-phase ultrastable mesoporous Y zeolite. The mass ratio of NaY zeolite to deionized water is preferably 1:5-10. The present invention does not specifically limit the drying temperature and drying time, for example, drying at 80-120°C overnight.
[0044] The total pore volume of the titanium-containing gas-phase ultrastable mesoporous Y zeolite obtained by the above method is 0.324-0.382 cm 3 / g, and the mesopore volume is 0.079~0.197cm 3 / g, and the proportion of mesopore volume to total pore volume is 21.0-61.0%.
[0045] The present invention not only avoids the defect of high price of template agent required for direct synthesis of mesoporous Y zeolite through the above preparation method, realizes the transformation of microporous Y zeolite to mesoporous Y zeolite in one step, but also introduces heteroatom titanium into the Y zeolite bulk phase, further improving the cracking performance of the zeolite. In addition, the mesoporous Y zeolite obtained by the method of the present invention has a low silicon-aluminum ratio and still retains a large number of acid centers. The heavy oil conversion ability of the FCC catalyst prepared as an active component is enhanced, and the yield of light oil is improved.
[0046] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solutions of the present invention are now further described with specific embodiments.
[0047] In each embodiment, the relative crystallinity and silicon-aluminum ratio of the Y-type zeolite obtained are determined as follows:
[0048] X-ray powder diffractometer was used, and the test conditions were: CuKα radiation, Ni filter, tube voltage 30kV, tube current 40Ma, step width 0.02, and the sum of the areas of eight peaks (331), (511 / 333), (440), (533), (642), (822, 660), (555, 751), (664) (compared with NaY zeolite standard) was used to calculate the sample crystallinity (relative crystallinity). The silicon-aluminum ratio was determined in accordance with the SH / T0339-92 standard method (see "Chemical Industry Standard Compilation", China Standards Press, published in 2000), and the unit cell constant was calculated according to the following formula:
[0049]
[0050] Where: α is the unit cell constant λ is u-Kα1; wavelength: (h 2 +k 2 +l 2) is the sum of squares of X-ray diffraction indexes. The silicon-aluminum ratio of Y-type zeolite is calculated according to the Breck-Flanigen formula: Si / Al=(25.858-α) / (α-24.191), SiO2, Al2O3=2×(Si / Al).
[0051] Example 1
[0052] This embodiment provides a titanium-containing gas-phase ultrastable mesoporous Y-type zeolite, which is prepared by the following steps:
[0053] Weigh 40.0 g of NaY zeolite dried overnight (provided by the catalyst plant of Lanzhou Petrochemical Company, the relative crystallinity of NaY zeolite is 97%, the unit cell constant is The skeleton silicon aluminum ratio is 5.1, and the Na2O content is 13.8wt%). It is placed in a quartz reaction tube, and dry high-purity nitrogen is introduced. The nitrogen purge rate is set to 50ml / min (glass rotor flowmeter). The temperature program of the tubular furnace reactor is set: from the starting temperature of 20°C, it is heated to 550°C for 53min and then maintained for 180min, and the temperature is naturally cooled to 450°C and then maintained at a constant temperature, and high-purity nitrogen saturated with TiCl4 is introduced, wherein the amount of titanium tetrachloride is 6.0g, and the contact time is 60min. After the reaction is completed, the high-purity nitrogen saturated with TiCl4 is stopped, and the high-purity nitrogen purge is continued for 120min and then the constant temperature is stopped. When the reactor is naturally cooled to below 200°C, the solid phase product is taken out and mixed with deionized water. The mass ratio of the product to deionized water is 1:5. The mixed slurry is stirred for 1h under 90°C water bath heating, and the filtrate is filtered until the filtrate is neutral. The filter cake is taken out and placed in a 120°C oven for overnight drying. Finally, titanium-containing gas-phase ultrastable mesoporous Y-type zeolite is obtained.
[0054] The Y-type zeolite obtained in this example was subjected to relevant test characterizations, and the results of its phase structure, texture properties, and elemental composition are listed in Table 1.
[0055] Example 2
[0056] This embodiment provides a titanium-containing gas-phase ultrastable mesoporous Y-type zeolite, which is prepared by the following steps:
[0057] Weigh 5.0 g of NaY zeolite dried overnight (provided by the catalyst plant of Lanzhou Petrochemical Company, the relative crystallinity of NaY zeolite is 97%, the unit cell constant is The skeleton silicon aluminum ratio is 5.1, and the Na2O content is 13.8wt%). It is placed in a quartz reaction tube, and high-purity nitrogen is introduced. After leak detection, the nitrogen purge rate is set to 50ml / min (glass rotor flowmeter), and the temperature program of the tubular furnace reactor is set: from the starting temperature of 20°C, it is heated to 500°C after 48min and then maintained for 60min, and the temperature is naturally cooled to 500°C and then maintained at a constant temperature, and high-purity nitrogen saturated with TiCl4 is introduced, wherein the amount of titanium tetrachloride is 1.0g, and the contact time is 120min. After the reaction is completed, the high-purity nitrogen saturated with TiCl4 is stopped, and the constant temperature is stopped after the high-purity nitrogen purge is continued for 120min. When the reactor is naturally cooled to below 200°C, the solid phase product is taken out and mixed with deionized water. The mass ratio of the product to deionized water is 1:10. The mixed slurry is stirred for 1h under 90°C water bath heating, and the filtrate is filtered until the filtrate is neutral. The filter cake is taken out and placed in a 120°C oven for overnight drying. Finally, titanium-containing gas-phase ultrastable mesoporous Y-type zeolite is obtained.
[0058] The Y-type zeolite obtained in this example was subjected to relevant test characterizations, and the results of its phase structure, texture properties, and elemental composition are listed in Table 1.
[0059] Example 3
[0060] This embodiment provides a titanium-containing gas-phase ultrastable mesoporous Y-type zeolite, which is prepared by the following steps:
[0061] Weigh 5.0 g of NaY zeolite dried overnight (provided by the catalyst plant of Lanzhou Petrochemical Company, the relative crystallinity of NaY zeolite is 97%, the unit cell constant is The skeleton silicon aluminum ratio is 5.1, and the Na2O content is 13.8wt%). It is placed in a quartz reaction tube, and high-purity nitrogen is introduced. After leak detection, the nitrogen purge rate is set to 50ml / min (glass rotor flowmeter), and the temperature rise program of the tubular furnace reactor is set: from the starting temperature of 20°C, the temperature is raised to 550°C after 53min and then maintained for 90min, and the temperature is naturally lowered to 410°C and then maintained at a constant temperature, and high-purity nitrogen saturated with TiCl4 is introduced, wherein the amount of titanium tetrachloride is 1.5g, and the contact time is 120min. After the reaction is completed, the high-purity nitrogen saturated with TiCl4 is stopped, and the constant temperature is stopped after the high-purity nitrogen purge is continued for 60min. When the reactor is naturally cooled to below 200°C, the solid phase product is taken out and mixed with deionized water. The mass ratio of the product to deionized water is 1:8. The mixed slurry is stirred for 1h under 90°C water bath heating, and the filtrate is filtered until the filtrate is neutral. The filter cake is taken out and placed in a 120°C oven for overnight drying. Finally, titanium-containing gas-phase ultrastable mesoporous Y-type zeolite is obtained.
[0062] The Y-type zeolite obtained in this example was subjected to relevant test characterizations, and the results of its phase structure, texture properties, and elemental composition are listed in Table 1.
[0063] Example 4
[0064] This embodiment provides a titanium-containing gas-phase ultrastable mesoporous Y-type zeolite, which is prepared by the following steps:
[0065] Weigh 5.0 g of NaY zeolite dried overnight (provided by the catalyst plant of Lanzhou Petrochemical Company, the relative crystallinity of NaY zeolite is 97%, the unit cell constant is The skeleton silicon aluminum ratio is 5.1, and the Na2O content is 13.8wt%). It is placed in a quartz reaction tube, and high-purity nitrogen is introduced. After leak detection, the nitrogen purge rate is set to 50ml / min (glass rotor flowmeter), and the temperature rise program of the tubular furnace reactor is set: from the starting temperature of 20°C, the temperature is raised to 550°C after 53min and then maintained for 60min, and the temperature is naturally reduced to 450°C and then maintained at a constant temperature, and high-purity nitrogen saturated with TiCl4 is introduced, wherein the amount of titanium tetrachloride is 3.0g, and the contact time is 120min. After the reaction is completed, the high-purity nitrogen saturated with TiCl4 is stopped, and the constant temperature is stopped after the high-purity nitrogen purge is continued for 60min. When the reactor is naturally cooled to below 200°C, the solid phase product is taken out and mixed with deionized water. The mass ratio of the product to deionized water is 1:5. The mixed slurry is stirred for 1h under 90°C water bath heating, and the filtrate is filtered until the filtrate is neutral. The filter cake is taken out and placed in a 120°C oven for overnight drying. Finally, titanium-containing gas-phase ultrastable mesoporous Y-type zeolite is obtained.
[0066] The Y-type zeolite obtained in this example was subjected to relevant test characterizations, and the results of its phase structure, texture properties, and elemental composition are listed in Table 1.
[0067] Example 5
[0068] This embodiment provides a titanium-containing gas-phase ultrastable mesoporous Y-type zeolite, which is prepared by the following steps:
[0069] Weigh 40.0 g of overnight dried RENaY zeolite (provided by the catalyst plant of Lanzhou Petrochemical Company, the relative crystallinity of RENaY zeolite is 88%, the unit cell constant is The skeleton silicon-aluminum ratio is 5.1, the Na2O content is 4.54wt%, the La2O3 content is 1.43wt%, and the CeO2 content is 1.21wt%) is placed in a quartz reaction tube, and high-purity nitrogen is introduced. After leak detection, the nitrogen purge rate is set to 50ml / min (glass rotor flowmeter), and the heating program of the tubular furnace reactor is set: from the starting temperature of 20°C, the temperature is increased to 550°C after 53min and then maintained for 60min, and the temperature is naturally reduced to 500°C and then maintained at a constant temperature, and high-purity nitrogen saturated with TiCl4 is introduced, wherein the titanium tetrachloride amount is 5.0g, and the contact time is 60min. After the reaction is completed, stop introducing high-purity nitrogen saturated with TiCl4, continue to purge with high-purity nitrogen for 60 minutes, and then stop constant temperature. When the reactor is naturally cooled to below 200°C, take out the solid phase product, mix it with deionized water, and the mass ratio of the product to deionized water is 1:10. Stir the mixed slurry in a 90°C water bath for 1 hour, filter until the filtrate is neutral, take out the filter cake and place it in a 120°C oven to dry overnight. Finally, the titanium-containing gas-phase ultra-stable mesoporous Y-type zeolite is obtained.
[0070] The Y-type zeolite obtained in this example was subjected to relevant test characterizations, and the results of its phase structure, texture properties, and elemental composition are listed in Table 1.
[0071] Example 6
[0072] This embodiment provides a titanium-containing gas-phase ultrastable mesoporous Y-type zeolite, which is prepared by the following steps:
[0073] Weigh 40.0 g of NaY zeolite dried overnight (provided by the catalyst plant of Lanzhou Petrochemical Company, the relative crystallinity of NaY zeolite is 97%, the unit cell constant is A skeleton silicon-aluminum ratio of 5.1, Na2O content of 13.8wt%) was placed in a quartz reaction tube, and high-purity nitrogen was introduced. After leak detection, the nitrogen purge rate was set to 50ml / min (glass rotor flowmeter), and the heating program of the tubular furnace reactor was set: from the starting temperature of 20°C, the temperature was increased to 550°C after 53min and then maintained for 60min, and the temperature was naturally reduced to 500°C and then maintained at a constant temperature, and high-purity nitrogen saturated with TiCl4 and SiCl4 gas was introduced, wherein the amount of titanium tetrachloride was 9.0g, the amount of silicon tetrachloride was 1.0g, and the contact time was 75min. After the reaction is completed, stop introducing high-purity nitrogen saturated with TiCl4 and SiCl4 gases, continue to purge with high-purity nitrogen for 120 minutes, and then stop constant temperature. When the reactor is naturally cooled to below 200°C, take out the solid phase product, mix it with deionized water, and the mass ratio of the product to deionized water is 1:10. Stir the mixed slurry in a 90°C water bath for 1 hour, filter until the filtrate is neutral, take out the filter cake and place it in a 120°C oven to dry overnight. Finally, titanium-containing gas-phase ultra-stable mesoporous Y-type zeolite is obtained.
[0074] The Y-type zeolite obtained in this example was subjected to relevant test characterizations, and the results of its phase structure, texture properties, and elemental composition are listed in Table 1.
[0075] Comparative Example 1
[0076] This comparative example provides a conventional gas-phase ultrastable Y-type zeolite obtained by reacting SiCl4 as a dealuminizing agent with NaY zeolite, which is prepared by the following steps:
[0077] Weigh 80.0 g of NaY zeolite dried overnight (provided by the catalyst plant of Lanzhou Petrochemical Company, the relative crystallinity of NaY zeolite is 97%, the unit cell constant is The skeleton silicon-aluminum ratio is 5.1, and the Na2O content is 13.8wt%) is placed in a quartz reaction tube, and high-purity nitrogen is introduced. After leak detection, the nitrogen purge rate is set to 50ml / min (glass rotor flowmeter), and the heating program of the tubular furnace reactor is set: from the starting temperature of 20°C, the temperature is increased to 550°C after 53min and then maintained for 120min, and the temperature is naturally reduced to 410°C and then maintained at a constant temperature, and high-purity nitrogen saturated with SiCl4 gas is introduced, wherein the amount of silicon tetrachloride is 12.0g, and the contact time is 120min. After the reaction is completed, stop introducing high-purity nitrogen saturated with SiCl4 gas, continue to purge with high-purity nitrogen for 120 minutes, and then stop constant temperature. When the reactor is naturally cooled to below 200°C, take out the solid phase product, mix it with deionized water, and the mass ratio of the product to deionized water is 1:10. Stir the mixed slurry in a 90°C water bath for 1 hour, filter until the filtrate is neutral, take out the filter cake and place it in a 120°C oven to dry overnight. Finally, ordinary gas-phase ultra-stable Y-type zeolite is obtained, which is recorded as DY zeolite.
[0078] The DY zeolite obtained in this comparative example was subjected to relevant test characterizations, and the results of its phase structure, texture properties, and elemental composition are listed in Table 1.
[0079] Comparative Example 2
[0080] This embodiment provides a method for preparing an ultrastable Y-type zeolite containing mesopores by a hydrothermal method, which is prepared by the following steps:
[0081] Weigh 100.0 g of NaY zeolite dried overnight (provided by the catalyst plant of Lanzhou Petrochemical Company, the relative crystallinity of NaY zeolite is 97%, the unit cell constant is The framework silicon-aluminum ratio is 5.1, and the Na2O content is 13.8wt%). It is mixed with ammonium chloride and deionized water in a mass ratio of 1:1:10, exchanged for 1 hour at a temperature of 90°C and a system pH of 3.1, and then filtered until the filtrate is neutral. After drying, 100% water vapor is introduced at 650°C and hydrothermally treated for 2 hours. The same steps are repeated once more to obtain a two-cross-two-hydrothermally ultrastable Y-type zeolite, which is denoted as USY zeolite.
[0082] The USY zeolite obtained in this comparative example was subjected to relevant test characterizations, and the results of its phase structure, texture properties, and elemental composition are listed in Table 1.
[0083] Embodiments 7 to 9
[0084] Examples 7 to 9 illustrate the heavy oil catalytic cracking performance of the Y-type zeolite provided by the present invention and the Y-type zeolites of Comparative Examples 1 and 2.
[0085] Catalyst preparation method:
[0086] On a dry basis, 35 wt% of zeolite, 15 wt% of aluminum sol and 50 wt% of kaolin were fully mixed, spray-formed and then hydrothermally aged at 800°C with 100% water vapor for 4 h. The aged catalyst was stored in a dry, anhydrous atmosphere for future use.
[0087] Reaction evaluation:
[0088] The reaction evaluation was carried out in a catalytic cracking fixed fluidized bed experimental device (ACE reaction evaluation device). The reaction raw material was the raw oil of the industrial catalytic cracking device (density (20°C) was 0.93 g / cm 3 , residual carbon 4.19wt%, saturated fraction 64.68wt%, aromatic fraction 28.44wt%, elemental analysis carbon content 86.76wt%, elemental analysis hydrogen content 11.63wt%), oil feed rate 1.5g, feed time 75s, catalyst-oil ratio 6, cracking reaction temperature 530°C. Cracking gas was analyzed online by gas chromatography. The carbon content on the catalyst was analyzed online. The composition of the collected liquid product was analyzed by simulated distillation chromatography.
[0089] Example 7
[0090] The titanium-containing gas-phase ultrastable mesoporous Y-type zeolite obtained in Example 3 was prepared into a catalyst according to the above catalyst preparation method, and the catalyst number was CAT-1. The reaction evaluation results are shown in Table 2.
[0091] Example 8
[0092] The gas-phase ultrastable Y-type zeolite obtained in Comparative Example 1 was prepared into a catalyst according to the above catalyst preparation method, and the catalyst number was CAT-2. The reaction evaluation results are shown in Table 2.
[0093] Example 9
[0094] The titanium-containing hydrothermal ultrastable mesoporous Y-type zeolite obtained in Comparative Example 2 was prepared into a catalyst according to the above catalyst preparation method, and the catalyst number was CAT-3. The reaction evaluation results are shown in Table 2.
[0095] Table 1 Phase structure, texture properties and elemental composition of samples obtained in Examples 1 to 6 and Comparative Examples 1 to 2
[0096]
[0097] As can be seen from Table 1, the Y-type zeolite prepared by the present invention has a considerable amount of mesopore volume, and the framework silicon-aluminum ratio is relatively low, retaining a large number of acidic centers. Compared with the hydrothermal ultrastable preparation process, it is simple, saves time, saves production costs, and is beneficial to environmental protection.
[0098] Table 2 ACE evaluation results of Examples 7 to 9
[0099]
[0100] a Conversion rate = (100-oil %) / 100
[0101] As can be seen from Table 2, the catalyst prepared from the Y-type zeolite obtained by the method of the present invention has a high conversion rate, a high light oil yield, and a low coke selectivity. Moreover, the catalyst prepared from the gas phase ultrastable product has a high light oil yield compared to the catalyst prepared from the hydrothermal ultrastable product.
[0102] Figure 1 The XRD spectra of Y zeolite obtained in Examples 1, 5 and 6 of the present invention are shown in FIG. Figure 1 It can be seen that the XRD spectra of the three samples of Example 1, Example 5 and Example 6 have the same characteristic emission peaks as the NaY standard sample.
[0103] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite, characterized in that: The preparation method consists of the following steps: Step 1, subjecting microporous NaY zeolite to a gas-solid reaction with titanium tetrachloride gas at a reaction temperature of 350 to 550° C. and a reaction time of 10 to 240 minutes; and Step 2: Wash the NaY zeolite after the reaction in step 1 with deionized water, filter and dry to obtain titanium-containing gas-phase ultrastable mesoporous Y zeolite.
2. The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite according to claim 1, characterized in that: The silicon-aluminum molar ratio of the microporous NaY zeolite is 4.5-5.5, calculated as the molar ratio of SiO2 to Al2O3; the dry basis Na2O content of the microporous NaY zeolite is 11-14 wt%; the total pore volume of the microporous NaY zeolite is not less than 0.250 cm 3 / g, BET specific surface area not less than 550m 2 / g.
3. The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite according to claim 1, characterized in that: The microporous NaY zeolite contains rare earth elements, the rare earth elements are calculated as RE2O3, the dry basis rare earth element content of the microporous NaY zeolite is 1-10wt%, and the Na2O content is not less than 5wt%; and / or the rare earth elements are one or both of lanthanum and cerium.
4. The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite according to claim 1, characterized in that: The microporous NaY zeolite is dried microporous NaY zeolite.
5. The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite according to claim 1, characterized in that: The titanium tetrachloride gas is introduced into the microporous NaY zeolite under the carrier of dry gas to carry out gas-solid reaction. The dry gas is one or a combination of two or more selected from the group consisting of nitrogen, air, argon and helium.
6. The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite according to claim 1, characterized in that: The mass ratio of the titanium tetrachloride gas to the microporous NaY zeolite dry basis is 0.1-0.8:
1.
7. The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite according to claim 1, characterized in that: The gas-solid reaction of the microporous NaY zeolite and the titanium tetrachloride gas includes a stage of gas-solid reaction of the microporous NaY zeolite and the continuously added titanium tetrachloride gas, and a stage of reaction of the microporous NaY zeolite under dry gas purge after the addition of titanium tetrachloride gas is stopped.
8. The method for preparing titanium-containing gas-phase ultrastable mesoporous Y zeolite according to claim 1, characterized in that: The NaY zeolite after the reaction is washed with deionized water, and the mass ratio of the NaY zeolite to the deionized water is 1:5-10. 9 . The titanium-containing gas-phase ultrastable mesoporous Y zeolite obtained by the preparation method of the titanium-containing gas-phase ultrastable mesoporous Y zeolite according to any one of claims 1 to 8 .
10. The titanium-containing gas-phase ultrastable mesoporous Y zeolite according to claim 9, characterized in that: The total pore volume of the titanium-containing gas-phase ultrastable mesoporous Y zeolite is 0.324 to 0.376 cm 3 / g, and the mesopore volume is 0.079~0.197cm 3 / g, and the proportion of mesopore volume to total pore volume is 21.0-60.8%.
11. Use of the titanium-containing gas-phase ultrastable mesoporous Y zeolite according to claim 9 or 10 as an acidic active component of a catalytic cracking catalyst.
Citation Information
Patent Citations
Y-type molecular sieve with ultra-high mesoporous content and preparation method of Y-type molecular sieve
CN104760973A
Y molecular sieve high in silica alumina ratio and abundant in secondary holes and preparation method therefor
CN104843736A
Rare earth zeolite Y and the preparation process thereof
US20030064881A1
Olefin epoxidation catalysts
US6114551A